Da'wah through documentary films produced by Malayan film unit (MFU) and filem negara Malaysia (FNM), 1957-1970 - Chellitda Farhana Gunaish; Mohd Firdaus Abdullah; Saifulazry Mokhtar; Norazilawati Abd Wahab; Azian Tahir (Kulliyyah of Islamic Revealed Knowledge and Human Sciences International Islamic University Malaysia, 2024)
This research aims to find out the role of documentary films produced by the Malayan Film Unit (MFU) and Filem Negara Malaysia (FNM) as a daʿwah medium in Malaysia and abroad from 1957 to 1970. The Department of Information Service and the Federation of Malaya Government collaborated with the Islamic Department of Malaya and the Islamic Department of Brunei to use MFU and FNM documentary films to develop an Islamic Malay community, which adhered to the actual teachings of Islam, during that time. Findings indicated that these documentary films by MFU and FNM were the early medium of daʿwah in the Federation of Malaya after the independent. It